دراسة تحويل الإحداثيات (3-D) المقيسة بنظام GPS من الجملة العالمية إلى إحداثيات في الجملة الستيريوغرافية السورية و برمجتها - محفوض, ندى (Latakia University Journal -Engineering Sciences Series, 2019)
يتضمن التحويل التشابهي (Conformal) لأنظمة الإحداثيات المتعامدة ثلاثية الأبعاد (3-D) كلاً من دوران المحاور الإحداثية، و تغير مقياس الرسم، وانزياح مبدأ الإحداثيات ، وبحيث يشكل هذا التحويل نموذجاً رياضياً عملياً للعلاقات بين مختلف أنظمة الإحداثيات المتعامدة (3-D) . و تعتمد التطبيقات الجيوديزية و التصويرية غالباً على نماذج التحويل المبسطة على اعتبار أن دوران المحاور يكون صغيراً أو مهملاً. تهدف الدراسة إلى عرض شامل لأنظمة الإحداثيات على سطح الأرض ، و التحويل بين هذه الأنظمة وكذلك شرح طريقة التربيعات الصغرى المستخدمة لتحديد متغيرات التحويل، و أخيراً كتابة برنامج بلغة Matlab لمعالجة الحالات المدروسة؛ مع تطبيق عددي يشرح آلية عمل البرنامج، و يبين مدى الوثوق بنتائجه. تشمل عملية التحويل بين أنظمة الإحداثيات على سطح الأرض كلاً مما يأتي : أولاً- التحويل من نظام إحداثيات جيوديزي إلى نظام إحداثيات متعامد محلي و العكس ( الحالة المدروسة الإسقاط الستيريوغرافي في سورية). ثانيا- التحويل من نظام إحداثيات جيوديزي إلى نظام إحداثيات متعامد مركزي و العكس. ثالثاً- التحويل التشابهي بين نظامي إحداثيات متعامدين مركزيين. The three dimensional (3–D) conformal coordinate system transformation combines axes rotations, scale change and shifts [of coordinates].Thus, this transformation is a practical mathematical model of the relationships involving different 3-D coordinate systems. Geocentric and graphic applications mainly rely on simple transformation models, given that axes-rotations are usually minimal or redundant. This paper aims at surveying the different coordinate systems on the globe and the rigorous development of the 3-D conformal transformation of coordinate systems (Geocentric, Local Topo-centric). In addition, this paper explains how least squares may be used in determining transformation parameters, and finally, a program has been written in Matlab to deal with all the cases mentioned above, in addition to the numerical application of the mechanism explaining the function of the program and the reliability of its results. The transformation process related to several coordinate systems involves the following: (1) Transformation from Geocentric to Local Topo-centric parameter systems and vice-versa [the case study of stereographic projection in Syria]; (2) Conformal transformation involving two Topo-centric coordinate systems.